A critical judgement of the applicability of 'New New Trade Theory' to agriculture: Structural change, productivity, and trade - Sören Prehn; Bernhard Brümmer (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2012)
The emergence of 'New New Trade Theory' fundamentally changed the thinking of international trade, and it is now at the heart of science. Here, we are going to take up the discussion of Golpinath et al. [2007], looking at whether 'New New Trade Theory' is applicable to agriculture. Revisiting the recent literature, we can find new theoretical and methodological evidence for its importance: the concepts of 'New New Trade Theory' will impact the modelling of structural change in agriculture and of agricultural trade. Farm productivity and agricultural trade cannot be seen anymore as detached from one another; both concepts are interrelated. We claim that 'New New Trade Theory' and its concepts will become standard for agriculture, too.
Keywords: 330; Agriculture Economics; New New Trade Theory; Farm Heterogeneity; Elasticity of Trade Flows; Estimation Methods